The position of the mental foramen towards the alveolar crest using digital panoramic radiographs - Farina Pramanik; Silmina Rukmana; Azhari Azhari (Ikatan Radiologi Kedokteran Gigi Indonesia, 2022)
Objectives: The rate of mandibular anesthesia failures is higher than maxilla, where the highest percentage is the inferior alveolar nerve block. One alternative action in case of failure is a mental nerve block, located in the mental foramen. Thus, knowledge of the mental foramen anatomy is required to avoid failure in anesthesia. The study is to determine the vertical and horizontal position of the mental foramen, which refers to the crest of the alveolar bone, using panoramic radiographs. Materials and Methods: The type of research that is used is descriptive with a purposive sampling method. The object of research is panoramic radiographs of patients who are in Dentistry Radiology Installation of Dental Hospital Universitas Padjadjaran, Bandung with a total sample of 352 panoramic radiographs. This research measured the vertical and horizontal distances between the mental foramen to the alveolar bone crest between 1st premolar teeth and 2nd premolar teeth. Results: The average value of the vertical distance mental foramen to the alveolar bone crest is 13,43 mm. The average value of the horizontal distance from mental foramen to 1st premolar teeth is 6,97 mm and the horizontal distance from mental foramen to 2nd premolar teeth is 2,80 mm. Conclusion: Mental foramen is closer to the 2nd premolar teeth based on the horizontal position and located below the apex based on the vertical position.